Validity of premature ejaculation diagnostic tool and its association with International Index of Erectile Function-15 in Chinese men with evidence-based-defined premature ejaculation - Tang, Dong-Dong (Asian J Androl, 2018)
The premature ejaculation diagnostic tool (PEDT) is a brief diagnostic measure to assess premature ejaculation (PE). However, there is insufficient evidence regarding its validity in the new evidence-based-defined PE. This study was performed to evaluate the validity of PEDT and its association with IIEF-15 in different types of evidence-based-defined PE. From June 2015 to January 2016, a total of 260 men complaining of PE and defined as lifelong PE (LPE)/acquired PE (APE) according to the evidence-based definition from Andrology Clinic of the First Affiliated Hospital of Anhui Medical University, along with 104 male healthy controls without PE from a medical examination center, were enrolled in this study. All individuals completed questionnaires including demographics, medical and sexual history, as well as PEDT and IIEF-15. After statistical analysis, it was found that men with PE reported higher PEDT scores (14.28 ± 3.05) and lower IIEF-15 (41.26 ± 8.20) than men without PE (PEDT: 5.32 ± 3.42, IIEF-15: 52.66 ± 6.86, P < 0.001 for both). It was suggested that a score of ≥9 indicated PE in both LPE and APE by sensitivity and specificity analyses (sensitivity: 0.875, 0.913; specificity: 0.865, 0.865, respectively). In addition, IIEF-15 were higher in men with LPE (42.64 ± 8.11) than APE (39.43 ± 7.84, P < 0.001). After adjusting for age, IIEF-15 was negatively related to PEDT in men with LPE (adjust r = −0.225, P < 0.001) and APE (adjust r = −0.378, P < 0.001). In this study, we concluded that PEDT was valid in the diagnosis of evidenced-based-defined PE. Furthermore, IIEF-15 was negatively related to PEDT in men with different types of PE.